Scientific rich images in translation: a multilingual study - Shuttleworth, Mark (The Journal of Specialised Translation, 2014)
The aim of this article is to investigate the solutions that translators opt for when translating metaphorical expressions that are classified as either 'rich images' or 'non-rich images.' The investigation is based on a corpus of Scientific American texts from 2003 and 2004 and their translations into French, Italian, German, Russian and Polish. Rich images are metaphorical expressions that are 'rich' in detail and in associations, and around 40% of the metaphors that occur in the corpus can be classified in this way. Based on a conceptual framework partially derived from metaphor research and on quantitative and qualitative analyses of the data, the article provides a list of translation procedures that the author identifies for the translation of rich images into non-rich images and vice versa. The article determines that there is a greater tendency for rich images to be replaced by non-rich than vice versa, thus leading to the conclusion that there is a general tendency to shift from the more to the less specific, in this area of translation practice at any rate.